Associations between social networks, cognitive function, and quality of life among older adults in long-term care - Laura Dodds; Carol Brayne; Joyce Siette (BMC Geriatrics, 2024)
Abstract Background Having rich social networks is associated with better physical and cognitive health, however older adults entering long-term care may experience an increased risk of social isolation and consequent negative impacts on cognitive function. Our study aimed to identify if there is an association between accessing specific types of services or activities within long-term care on social networks and cognition. Methods A cross-sectional study of 96 residents from 2 aged care providers in New South Wales, Australia. Residents were given a battery of assessments measuring social network structure (Lubben Social Network Scale, LSNS-12), quality of life (EuroQol 5D, Eq. 5D5L) and cognitive function (Montreal Cognitive Assessment, MoCA). Demographic factors and service use factors were also collected from aged care providers’ electronic records. Independent sample t-test, ANOVA and linear regression analyses were used to explore associated factors for cognition. Results Residents had a mean age of 82.7 ± 9.4 years (median = 81) and 64.6% were women. Most residents had cognitive impairment (70.8%) and reported moderate sized social networks (26.7/60) (Lubben Social Network Scale, LSNS-12). Residents who had larger social networks of both family and friends had significantly better cognitive performance. Service type and frequency of attendance were not associated with cognitive function. Conclusions Among individuals most at risk of social isolation, having supportive and fulfilling social networks was associated with preserved cognitive function. The relationship between service provision and social interactions that offer psychosocial support within long-term facilities and its impact over time on cognitive function requires further exploration.